Pelaksanaan Inisiasi Menyusui Dini Pada Ibu Post Partum Di Desa Sooko Kecamatan Sooko Kabupaten Mojokerto - Farida Yuliani (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2013)
In Indonesia showed 95% of children under 5 years old ever got breastfed. However, only 44% who got breastfed in the first hour after birth and only 62% who got breastfed in the first days after birth. The purpose of this research was conducted to determine the early initiation of suckling, in the village of Sooko Mojokerto district of Sooko conducted on May 6 to 6 June 2013. The research used descriptive research. The variables examined is early initiation of suckling's implementation. The population in this study as many as 14 respondents, how to capture sample using a nonprobability sampling in the form of saturated/total sampling. The data is then processed with the editting, coding, data entry, scoring, cleaning, release information, and tabulating. Data is analyzed using fisher's exact probability test. Results showed that respondents who got family support with implementing early initiation of suckling as many as 5 respondents (35,8%) and respondents who did not support the family by not implementing the early initiation of suckling as many as 7 respondents (50%). Breastfeeding mothers need support informational, emotional, instrumental, and the assessment of the family in the performance of early initiation of suckling. Families play a role in determining fluency reflex spending ASI which strongly influenced by emotional state or feeling of mother. Improvement of services to provide information and counseling especially in the elderly and the husband in providing motivation, perception, and attitudes to the mother about the importance of early breastfeeding initiation.